Lung function and its determinants among human immunodeficiency virus patients on antiretroviral therapy - Ulandari, I Gusti Ayu Putu Putri; Somia, I Ketut Agus; Wesnawa, Made Agustya Darma Putra; Candrawati, Ni Wayan; Kusumawardani, Ida Ayu Jasminarti Dwi; Arisanti, Ni Luh Putu Eka (Edelweiss Applied Science and Technology, 2025)
HIV patients face an increased risk of lung impairment due to chronic inflammation and opportunistic infections, yet factors influencing abnormal lung function in those receiving antiretroviral therapy (ART) remain unclear. This cross-sectional study examined HIV-infected adults (≥18 years) on ART at Ngoerah Hospital (January-March 2025). Patients with active tuberculosis, respiratory infections, or spirometry contraindications were excluded. Participants underwent clinical evaluation and spirometry using Contec SP80B. Multivariate logistic regression identified risk factors for abnormal lung function. Among the 183 participants, 102 (55.74%) had normal lung function. Abnormalities included restrictive disorders (60 patients, 32.79%), obstructive disorders (8 patients, 4.37%), and mixed patterns (13 patients, 7.10%). A prior lung infection history was the sole independent risk factor for abnormal lung function (AOR 7.221; 95% CI: 2.444–21.336; p < 0.001). Age, sex, BMI, smoking, drug use, non-infectious lung disease history, HIV stage, CD4+ count, viral load, ART regimen, and treatment duration showed no significant associations (p > 0.05). Lung function abnormalities are prevalent among HIV patients on ART, with prior lung infections being a key determinant. These findings support the need for routine lung function monitoring in this population, particularly those with a history of lung infections.